2006
DOI: 10.1111/j.1348-0421.2006.tb03791.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Effect of the Propionibacterium acnes and Its Purified Soluble Polysaccharide on the Immunization with Plasmidial DNA Containing a Trypanosoma cruzi Gene

Abstract: In the present work we investigated the role of killed Propionibacterium acnes or a soluble polysaccharide extracted from bacterium cell wall in modulated experimental immunization with plasmidial DNA. We used a plasmid, p154/13, containing a gene‐encoding catalytic domain of Trypanosoma cruzi (T. cruzi) trans‐sialidase. As previously described, immunization of BALB/c mice with p154/13 elicited humoral, cell‐mediated and protective immune responses against T. cruzi infection. In this study we describe that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 32 publications
2
38
1
1
Order By: Relevance
“…Moreover, P. acnes is rarely identified as a cause of significant infection (11). In the present study, P. acnes induced biological effects that modulate the innate and acquired immune responses, causing increased phagocytic and tumoricidal activities in macrophages (12)(13)(14), increased antibody responses (15,16), and increased resistance to different pathogens (15,17). Therefore, the use of P. acnes and its components as immune enhancers and antineoplastic agents has become a focus in clinical and basic research.…”
mentioning
confidence: 69%
“…Moreover, P. acnes is rarely identified as a cause of significant infection (11). In the present study, P. acnes induced biological effects that modulate the innate and acquired immune responses, causing increased phagocytic and tumoricidal activities in macrophages (12)(13)(14), increased antibody responses (15,16), and increased resistance to different pathogens (15,17). Therefore, the use of P. acnes and its components as immune enhancers and antineoplastic agents has become a focus in clinical and basic research.…”
mentioning
confidence: 69%
“…This polysaccharide, similarly to the whole bacterium, increased nitric oxide (NO) and TNF-␣ synthesis, enhanced phagocytic activity by peritoneal macrophages and promoted resistance to infection [38]. We also observed that PS was a major P. acnes component responsible for bacterium adjuvant effect to antibody response and IFN-␥ production on a Trypanosoma cruzi DNA vaccine [24]. Besides, P. acnes and PS were able to modulate the number of different peritoneal cell populations and their functions, including macrophage tumoricidal activity [22].…”
Section: Introductionmentioning
confidence: 82%
“…In our laboratory, we purified a soluble polysaccharide phenol-extracted from P. acnes cell wall which induces similar effects to the whole bacterium [22,24,38,39]. However, the fine structural characterization of this compound had not yet been performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations